In search of an idea. What is 'community' in 'community-based management’ and how to improve our understanding of it for the sake of sustainable management? !Xun, Khwe and Wildebeest Kuil rock art site - (:unkn) unknown (My University, 2024)
This communication analyses the dynamics surrounding the involvement of two San communities, the !Xun and the Khwe, in the management of the Wildebeest Kuil rock art site since 2001. Despite this initiative, the !Xun and the Khwe quickly lost interest in the site. With regard to heritage resource management issues, this paper draws on this specific case study to question the uses and abuses of the notion of 'community'. From this case study, we will see how the !Xun and the Khwe of Platfontein are sometimes considered as one community, sometimes as two communities. This matter of understanding is examined in relation to the Wildebeest Kuil rock art site. Rather than imposing preconceived ideas about what constitutes a community, this communication proposes an exploration of the dynamics surrounding this rock art site, in order to question where the community is, who makes it exist, and how it takes shape. From this rock art site, we will thus inform different existing conceptions of community (legal, anthropological), before presenting a third approach (pragmatic), one which is more realistic for our research activities, providing useful theoretical insights for action in response to cultural heritage management challenges. In terms of methods, this communication mobilises qualitative data from field observations and semi-structured interviews with various stakeholders and analysis of grey literature. It is based both on research carried out as part of a Master's thesis and on analyses carried out by the COSMO-ART research group (a project funded by the French research agency involving South-African, Namibian and French researchers).
Keywords: African Research